Recent developments in organocatalysed transformations of epoxides and carbon dioxide into cyclic carbonates. Issue 1 (17th December 2020) - Guo, Liping; Lamb, Katie J.; North, Michael
Abstract : The synthesis of cyclic carbonates from epoxides and carbon dioxide using metal-free catalyst systems is critically reviewed. Abstract : This review is focused on the rapidly developing area of organocatalysed cyclic carbonate synthesis. It starts with an introduction to carbon capture and utilisation in general, which introduces the importance of cyclic carbonates. The various mechanisms for cyclic carbonate synthesis are next discussed with a focus on the relative and absolute stereochemical consequences of each mechanism and how this combined with other physical organic chemistry techniques can be used to distinguish between three main mechanistic classes: epoxide activation; carbon dioxide activation and dual activation. Section 2 of the review then discusses recently reported homogeneous organocatalysed systems whilst section 3 surveys recently reported heterogeneous catalyst systems. For each catalyst system, the mechanism of action is discussed with reference to the mechanisms introduced at the start of the review and key parameters such as the optimal temperature, pressure and catalyst loading are given combined with information on substrate scope and yields. This allows the various catalysts to be critically compared on the basis of whichever parameter(s) are of most significance to the reader. A Final Thoughts/Perspective section focusses on the limitations of the use of turnover frequency and turnover number to compare catalysts in this reaction and makes the case for authors to use of a wider range of green metrics when reporting new catalysts. Finally, the Conclusions section focuses on future challenges such as the use of biomass derived epoxides, use of impure carbon dioxide and the need to develop new and existing highly active catalysts out of the laboratory and into real world applications.